New species and new records of Mesoceration Janssens, 1967 from South Africa (Coleoptera, Hydraenidae) - Bilton, David T. (Zootaxa, 2015)
Mesoceration Janssens, 1967 is the most speciose genus of Prosthetopinae, most of the 44 described species being restricted to South Africa, and almost all occupying the benthic zone of streams and rivers. Here seven species are described as new: Mesoceration caniplenum sp. nov., M. foggoi sp. nov., M. helmei sp. nov., M. hirsutum sp. nov., M. rugulosum sp. nov., M. sewefonteinense sp. nov. and M. sinclairi sp. nov., bringing the number of known species to 51. All seven new species have been discovered during recent, targeted sampling of South African Hydraenidae. New collection records resulting from this fieldwork are also provided for 27 previously described species, together with ecological notes.